(untitled) (RT. A Journal on Research Policy and Evaluation, 2016)
The changes in the legal status and in the recruiting procedures of Italian University professors and researchers occurred in the last forty years are summarily described. The related recruiting policies are analyzed in detail, reporting yearly data on recruitment and on the (growing) average age of access to the different roles. Data on the quantitative evolution of the academic staff and on its constant aging are presented (and discussed) on a yearly basis from the early Eighties to the year 2015. The distinct evolution of different scientific areas is analyzed. Gender effects (and in particular the “glass ceiling”) are considered. The most significant changes in the geographic distribution of Universities and of their teaching body (from the year 1939 to the present day) are described. Some general conclusions on the Italian University system and its recent evolution are drawn